THE ROLE OF INFORMATION WARFARE IN MODERN WARFARE - Erkayev Berdiyor Yuldashevich (Bright Mind Publishing, 2025)
This article analyzes the role, means and strategic importance of information warfare in modern warfare. Information warfare is seen as an important piece of military action, explaining how it works through cybersecurity, psychological impact, and propaganda on social media. The real impact of information warfare is illustrated by the example of the Ukraine-Russia war. The article also discusses the dangers and opportunities of information warfare.
Keywords: Information warfare, disinformation, cybersecurity, psychological operations, media strategy, modern warfare.